Electrochemical characterization of phthalocyanine derivatives carrying a bulky triester unit on each benzo group - KOCA, ATIF (SPRINGER, 2005)
The focus of the present work is to gain more insight into the electrochemical behavior of newly synthesized Co-II, Zn-II, Cu-II, and Pd-II phthalocyanines with tetra-tricarbethoxyethyl substituents at the peripheral position. A more exhaustive electrochemical study of the complexes was done to determine the desired wisdom for the usage of the complexes as a functional material. A comparative study of the voltammetric measurements of these complexes showed that while Zn-II, Cu-II, and Pd-II phthalocyanines exhibited up to four common phthalocyanine ring reductions, Co-II phthalocyanine gave a metal-centered oxidation, a reduction and a ligand-centered reduction process. By contrast observation of the splitting of the second reduction process of Pd-II phthalocyanine suggests aggregation of the complex. Diffusion coefficients of all complexes were determined by both the cyclic voltammetry and the potential step chronocoulometry techniques. Diffusion coefficients of the reduced and oxidized forms of the redox couples of the complexes were also calculated by the potential step chronocoulometry technique. Diffusion coefficients of the reduced forms of the electrode products of the complexes were found to be slightly higher than that of the oxidized forms.
Keywords: FERROUS PHTHALOCYANINE; COBALT PHTHALOCYANINE; REPLACEMENT REACTIONS; METALLOPHTHALOCYANINES; PORPHYRAZINES; ADSORPTION